Group Rumination: Social Interactions Around Music in People with Depression - Garrido, Sandra; Eerola, Tuomas; McFerran, Katrina (Frontiers in Psychology, 2017)
One of the primary functions that music serves in human society is the promotion of social relationships and group cohesion. In general, emotional experiences tend to be amplified in group settings through processes of social feedback. However, previous research has established that listening to sad music can intensify negative emotions in people with tendencies to rumination and depression. This study therefore investigated the phenomenon of ruminating with music, and the question of whether listening to sad music in group settings provides social benefits for emotionally vulnerable listeners, or whether it further exaggerates depressive tendencies. Participants recruited via online depression groups and mental health websites were surveyed as to music listening habits. Results revealed that people with depression were more likely to engage in ‘group rumination’ using music, and that this behavior could be partially explained by a general tendency to ruminate using music. Both affective states and coping styles were found to be related to the affective outcomes of group interactions around music. These findings go some way towards clarifying the situations in which group interactions with music are able to provide important social benefits for those involved, and situations in which negative emotions can be amplified by the group context.